Insulator and low-temperature sintering process thereof

CN117766240BActive Publication Date: 2026-10-13HUNAN HUDIAN POWER EQUIP CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311600213.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-11-28
Publication Date
2026-10-13
Estimated Expiration
2043-11-28

AI Technical Summary

Technical Problem

上述方法中使用涂料的方法使绝缘子具备超疏水性能,虽然实验室中性能优异,但是涂料在野外恶劣环境下容易被风霜雨雪所腐蚀损耗失去作用,造成污物的积累,并且上述涂料与绝缘子的结合性能也会随着时间而减弱,更容易在恶劣环境中脱落

Benefits of technology

[0019]本发明提供了一种绝缘子及其低温烧结工艺,由陶瓷芯体和自清洁外层组成,自清洁层中的氢氧化铝经过改性,自清洁外层的疏水性,介电常数,硬度以及平衡拉伸强度和断裂伸长率均得到很大改善,并且本发明通过将自清洁外层低温烧结至陶瓷芯体上,使得自清洁外层牢固的结合在陶瓷芯体上,不易受外界环境影响而老化脱落,自清洁能力强,绝缘效果好,制备成本低,寿命长。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117766240B_ABST
    Figure CN117766240B_ABST
Patent Text Reader

Abstract

The application belongs to the field of insulators, and particularly discloses an insulator and a low-temperature sintering process thereof. The insulator is composed of a ceramic core and a self-cleaning outer layer. The self-cleaning outer layer is made of the following basic raw materials in parts by weight: 100 parts of high-temperature vulcanized silicone rubber, 30-60 parts of aluminum hydroxide, 20-40 parts of zinc oxide, 10-20 parts of polylactic acid-glycolic acid copolymer, 5-10 parts of lanthanum oxide and 4-8 parts of vinyl bis-stearamide. The insulator disclosed by the application is sintered at low temperature to the ceramic core to firmly combine the self-cleaning outer layer to the ceramic core, so that the self-cleaning outer layer is not easy to age and fall off under the influence of the external environment, has strong self-cleaning ability, good insulation effect, low preparation cost and long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of insulators, and specifically discloses an insulator and its low-temperature sintering process. Background Technology

[0002] An insulator is a device installed between conductors at different potentials or between a conductor and a grounding component, capable of withstanding voltage and mechanical stress. Pollution flashover refers to the phenomenon where contaminants adhering to the insulating surface of electrical equipment gradually dissolve in water under humid conditions, forming a conductive film on the insulating surface. This significantly reduces the insulation level of the insulator, leading to a strong discharge phenomenon under the influence of an electric field. There are many measures to prevent pollution flashover. Traditional methods include power outages and cleaning in spring and autumn, the use of silicone oil, silicone grease, and other coatings, and the proper adjustment of the creepage distance of the external insulation. Recent methods include the use of anti-flashover creepage skirts and RTV anti-pollution flashover coatings. CN201610270033.7 discloses a superhydrophobic coating and an anti-pollution flashover superhydrophobic insulator and its preparation process. The insulator includes a surface modification layer on its outer surface and a superhydrophobic coating on the surface modification layer. The surface modification layer is made of a surface modification liquid, which consists of a surface modifier propyltrimethoxysilane and ethanol in a mass ratio of 1:15-20. The superhydrophobic coating is made of nano-silica superhydrophobic coating. The above-mentioned method uses coatings to give insulators superhydrophobic properties. Although the coatings perform excellently in the laboratory, they are easily corroded and worn away by wind, frost, rain, and snow in harsh outdoor environments, leading to the accumulation of dirt. Furthermore, the adhesion between the coating and the insulator weakens over time, making it more prone to peeling off in harsh environments. In addition, the above methods require multiple surface treatments of the insulator, making the process complex, and the coatings themselves pollute the environment. Therefore, the above methods have many drawbacks. Summary of the Invention

[0003] To address the aforementioned problems, this invention discloses an insulator and its low-temperature sintering process. By sintering a self-cleaning outer layer onto a ceramic core at a low temperature, the self-cleaning outer layer is firmly bonded to the ceramic core and is less susceptible to aging and detachment due to external environmental influences.

[0004] This invention includes the following technical solutions:

[0005] An insulator comprising a ceramic core and a self-cleaning outer layer, wherein the self-cleaning outer layer is made of the following base materials in parts by weight:

[0006]

[0007]

[0008] Furthermore, in the aforementioned insulator, the polylactic acid-glycolic acid copolymer is composed of 50-75% lactic acid and 25-50% glycolic acid.

[0009] Furthermore, in the aforementioned insulator, the high-temperature vulcanized silicone rubber is methylphenyl vinyl silicone rubber, with a phenyl content of 15-25 mol% and a vinyl content of 0.16%-0.23%.

[0010] Furthermore, the low-temperature sintering process of the above-mentioned insulator includes the following steps: (1) Preparation of modified aluminum hydroxide: Polylactic acid-hydroxyacetic acid copolymer and tetrachloromethane are mixed evenly to obtain a mixture, aluminum hydroxide powder is added, ultrasonic vibration is performed for 5 to 10 minutes to obtain a suspension, emulsifier is added, stirring is performed, and the filter residue is obtained by suction filtration. The filter residue is washed with anhydrous ethanol 3 to 5 times and placed in an oven at 60 to 80°C to dry to constant weight to obtain modified aluminum hydroxide;

[0011] (2) Preparation of self-cleaning coating: Modified aluminum hydroxide, zinc oxide, lanthanum oxide and high-temperature vulcanized silicone rubber are mixed and ball-milled for 10-30 min to obtain mixed powder; vinyl bis-stearamide and deionized water are mixed at a mass ratio of 1:10-40, ultrasonically dispersed and stirred to obtain dispersion; the mixed powder and dispersion are mixed, high-speed sheared and ultrasonically treated to obtain self-cleaning coating;

[0012] (3) Low-temperature sintering: The ceramic core is cleaned to obtain clean ceramic. A self-cleaning coating is applied to the surface of the clean ceramic to form a self-cleaning film. The ceramic is then calcined at a low temperature of 220-260℃ for 4-8 hours and cooled to obtain the insulator.

[0013] Furthermore, in the aforementioned low-temperature sintering process, the thickness of the self-cleaning film layer is 0.5-2 mm.

[0014] Furthermore, in the above-mentioned low-temperature sintering process, the mass ratio of the polylactic acid-hydroxyacetic acid copolymer to tetrachloromethane is 1:2-10.

[0015] Furthermore, in the aforementioned low-temperature sintering process, the emulsifier is polyoxypropylene ether.

[0016] Furthermore, in the aforementioned low-temperature sintering process, the mass ratio of the polyoxypropylene ether to the suspension is 1:5-10.

[0017] Furthermore, in the aforementioned low-temperature sintering process, the ceramic core is a zirconia ceramic core.

[0018] Compared with the prior art, the present invention has the following beneficial effects:

[0019] This invention provides an insulator and its low-temperature sintering process, consisting of a ceramic core and a self-cleaning outer layer. The aluminum hydroxide in the self-cleaning layer is modified, which greatly improves the hydrophobicity, dielectric constant, hardness, equilibrium tensile strength, and elongation at break of the self-cleaning outer layer. Furthermore, by sintering the self-cleaning outer layer onto the ceramic core at low temperature, the self-cleaning outer layer is firmly bonded to the ceramic core, making it less susceptible to aging and detachment due to external environmental influences. It exhibits strong self-cleaning ability, good insulation performance, low manufacturing cost, and long service life. Attached Figure Description

[0020] Figure 1 Comparative test diagrams of relative permittivity kV / mm (1mm) for test examples;

[0021] Figure 2 Comparison test diagram of tensile strength (MPa) of test examples;

[0022] Figure 3 Comparative test chart of elongation at break (%) in test examples;

[0023] Figure 4 Comparison test chart of tear strength kN / m for test examples. Detailed Implementation

[0024] An insulator comprising a ceramic core and a self-cleaning outer layer, wherein the self-cleaning outer layer is made of the following base materials in parts by weight:

[0025]

[0026] The polylactic acid-glycolic acid copolymer is composed of 50-75% lactic acid and 25-50% glycolic acid.

[0027] The high-temperature vulcanized silicone rubber is methylphenyl vinyl silicone rubber, with a phenyl content of 15-25 mol% and a vinyl content of 0.16%-0.23%.

[0028] The low-temperature sintering process of the above insulators:

[0029] (1) Preparation of modified aluminum hydroxide: Polylactic acid-hydroxyacetic acid copolymer and tetrachloromethane are mixed evenly to obtain a mixture. Aluminum hydroxide powder is added and ultrasonically vibrated for 5-10 min to obtain a suspension. Emulsifier is added, the mixture is stirred and filtered to obtain a filter residue. The filter residue is washed with anhydrous ethanol 3-5 times and dried in an oven at 60-80℃ to constant weight to obtain modified aluminum hydroxide.

[0030] (2) Preparation of self-cleaning coating: Modified aluminum hydroxide, zinc oxide, lanthanum oxide and high-temperature vulcanized silicone rubber are mixed and ball-milled for 10-30 min to obtain mixed powder; vinyl bis-stearamide and deionized water are mixed at a mass ratio of 1:10-40, ultrasonically dispersed and stirred to obtain dispersion; the mixed powder and dispersion are mixed, high-speed sheared and ultrasonically treated to obtain self-cleaning coating;

[0031] (3) Low-temperature sintering: The ceramic core is cleaned to obtain clean ceramic. A self-cleaning coating is applied to the surface of the clean ceramic to form a self-cleaning film. The ceramic is then calcined at a low temperature of 220-260℃ for 4-8 hours and cooled to obtain the insulator.

[0032] The thickness of the self-cleaning membrane layer is 0.5-2 mm;

[0033] The mass ratio of the polylactic acid-glycolic acid copolymer to tetrachloromethane is 1:2-10;

[0034] The emulsifier is polyoxypropylene ether;

[0035] The mass ratio of the polyoxypropylene ether to the suspension is 1:5-10;

[0036] The ceramic core is a zirconia ceramic core.

[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0038] Example 1

[0039] An insulator comprising a ceramic core and a self-cleaning outer layer, wherein the self-cleaning outer layer is made of the following base materials in parts by weight:

[0040]

[0041] The polylactic acid-glycolic acid copolymer is composed of 50% lactic acid and 50% glycolic acid.

[0042] The high-temperature vulcanized silicone rubber is methylphenyl vinyl silicone rubber, with a phenyl content of 15 mol% and a vinyl content of 0.16%.

[0043] The low-temperature sintering process of the above insulators:

[0044] (1) Preparation of modified aluminum hydroxide: Polylactic acid-hydroxyacetic acid copolymer and tetrachloromethane are mixed evenly to obtain a mixture. Aluminum hydroxide powder is added and ultrasonically vibrated for 5-10 min to obtain a suspension. Emulsifier is added, the mixture is stirred and filtered to obtain a filter residue. The filter residue is washed with anhydrous ethanol 3-5 times and dried in an oven at 60-80℃ to constant weight to obtain modified aluminum hydroxide.

[0045] (2) Preparation of self-cleaning coating: Modified aluminum hydroxide, zinc oxide, lanthanum oxide and high-temperature vulcanized silicone rubber are mixed and ball-milled for 10-30 min to obtain mixed powder; vinyl bis-stearamide and deionized water are mixed at a mass ratio of 1:10, ultrasonically dispersed and stirred to obtain dispersion; the mixed powder and dispersion are mixed, high-speed sheared and ultrasonically treated to obtain self-cleaning coating.

[0046] (3) Low-temperature sintering: The ceramic core is cleaned to obtain clean ceramic. A self-cleaning coating is applied to the surface of the clean ceramic to form a self-cleaning film. The ceramic is then calcined at a low temperature of 220-260℃ for 4-8 hours and cooled to obtain the insulator.

[0047] The thickness of the self-cleaning membrane is 1 mm;

[0048] The mass ratio of the polylactic acid-glycolic acid copolymer to tetrachloromethane is 1:2;

[0049] The emulsifier is polyoxypropylene ether;

[0050] The mass ratio of the polyoxypropylene ether to the suspension is 1:5;

[0051] The ceramic core is a zirconia ceramic core.

[0052] Example 2

[0053] An insulator comprising a ceramic core and a self-cleaning outer layer, wherein the self-cleaning outer layer is made of the following base materials in parts by weight:

[0054]

[0055] The polylactic acid-glycolic acid copolymer is composed of 60% lactic acid and 40% glycolic acid.

[0056] The high-temperature vulcanized silicone rubber is methylphenyl vinyl silicone rubber, with a phenyl content of 20 mol% and a vinyl content of 0.20%.

[0057] The low-temperature sintering process of the above insulators:

[0058] (1) Preparation of modified aluminum hydroxide: Polylactic acid-hydroxyacetic acid copolymer and tetrachloromethane are mixed evenly to obtain a mixture. Aluminum hydroxide powder is added and ultrasonically vibrated for 5-10 min to obtain a suspension. Emulsifier is added, the mixture is stirred and filtered to obtain a filter residue. The filter residue is washed with anhydrous ethanol 3-5 times and dried in an oven at 60-80℃ to constant weight to obtain modified aluminum hydroxide.

[0059] (2) Preparation of self-cleaning coating: Modified aluminum hydroxide, zinc oxide, lanthanum oxide and high-temperature vulcanized silicone rubber are mixed and ball-milled for 10-30 min to obtain mixed powder; vinyl bis-stearamide and deionized water are mixed at a mass ratio of 1:20, ultrasonically dispersed and stirred to obtain dispersion; the mixed powder and dispersion are mixed, high-speed sheared and ultrasonically treated to obtain self-cleaning coating.

[0060] (3) Low-temperature sintering: The ceramic core is cleaned to obtain clean ceramic. A self-cleaning coating is applied to the surface of the clean ceramic to form a self-cleaning film. The ceramic is then calcined at a low temperature of 220-260℃ for 4-8 hours and cooled to obtain the insulator.

[0061] The thickness of the self-cleaning membrane is 1 mm;

[0062] The mass ratio of the polylactic acid-glycolic acid copolymer to tetrachloromethane is 1:5;

[0063] The emulsifier is polyoxypropylene ether;

[0064] The mass ratio of the polyoxypropylene ether to the suspension is 1:7;

[0065] The ceramic core is a zirconia ceramic core.

[0066] Example 3

[0067] An insulator comprising a ceramic core and a self-cleaning outer layer, wherein the self-cleaning outer layer is made of the following base materials in parts by weight:

[0068]

[0069] The polylactic acid-glycolic acid copolymer is composed of 75% lactic acid and 25% glycolic acid.

[0070] The high-temperature vulcanized silicone rubber is methylphenyl vinyl silicone rubber, with a phenyl content of 25 mol% and a vinyl content of 0.23%.

[0071] The low-temperature sintering process of the above insulators:

[0072] (1) Preparation of modified aluminum hydroxide: Polylactic acid-hydroxyacetic acid copolymer and tetrachloromethane are mixed evenly to obtain a mixture. Aluminum hydroxide powder is added and ultrasonically vibrated for 5-10 min to obtain a suspension. Emulsifier is added, the mixture is stirred and filtered to obtain a filter residue. The filter residue is washed with anhydrous ethanol 3-5 times and dried in an oven at 60-80℃ to constant weight to obtain modified aluminum hydroxide.

[0073] (2) Preparation of self-cleaning coating: Modified aluminum hydroxide, zinc oxide, lanthanum oxide and high-temperature vulcanized silicone rubber are mixed and ball-milled for 10-30 min to obtain mixed powder; vinyl bis-stearamide and deionized water are mixed at a mass ratio of 1:40, ultrasonically dispersed and stirred to obtain dispersion; the mixed powder and dispersion are mixed, high-speed sheared and ultrasonically treated to obtain self-cleaning coating.

[0074] (3) Low-temperature sintering: The ceramic core is cleaned to obtain clean ceramic. A self-cleaning coating is applied to the surface of the clean ceramic to form a self-cleaning film. The ceramic is then calcined at a low temperature of 220-260℃ for 4-8 hours and cooled to obtain the insulator.

[0075] The thickness of the self-cleaning membrane is 1 mm;

[0076] The mass ratio of the polylactic acid-glycolic acid copolymer to tetrachloromethane is 1:10;

[0077] The emulsifier is polyoxypropylene ether;

[0078] The mass ratio of the polyoxypropylene ether to the suspension is 1:10;

[0079] The ceramic core is a zirconia ceramic core.

[0080] Comparative Example 1

[0081] An insulator comprising a ceramic core and a self-cleaning outer layer, wherein the self-cleaning outer layer is made of the following base materials in parts by weight:

[0082]

[0083] The high-temperature vulcanized silicone rubber is methylphenyl vinyl silicone rubber, with a phenyl content of 20 mol% and a vinyl content of 0.20%.

[0084] The low-temperature sintering process of the above insulators:

[0085] (2) Preparation of self-cleaning coating: aluminum hydroxide, zinc oxide, lanthanum oxide and high-temperature vulcanized silicone rubber are mixed and ball-milled for 10-30 min to obtain mixed powder; vinyl bis-stearamide and deionized water are mixed at a mass ratio of 1:20, ultrasonically dispersed and stirred to obtain dispersion; the mixed powder and dispersion are mixed, high-speed sheared and ultrasonically treated to obtain self-cleaning coating.

[0086] (3) Low-temperature sintering: The ceramic core is cleaned to obtain clean ceramic. A self-cleaning coating is applied to the surface of the clean ceramic to form a self-cleaning film. The ceramic is then calcined at a low temperature of 220-260℃ for 4-8 hours and cooled to obtain the insulator.

[0087] The thickness of the self-cleaning membrane is 1 mm;

[0088] The emulsifier is polyoxypropylene ether;

[0089] The mass ratio of the polyoxypropylene ether to the suspension is 1:7;

[0090] The ceramic core is a zirconia ceramic core.

[0091] Compared to Example 2, this comparative example does not contain modified aluminum hydroxide.

[0092] Comparative Example 2

[0093] Commercially purchased insulator anti-pollution flashover coating Silshan 2S3M, a long-lasting anti-pollution flashover coating for silicone rubber, was applied to the zirconia ceramic core according to the instructions.

[0094] Test case

[0095] The insulators prepared in Examples 1-3 and Comparative Examples 1-2 were subjected to performance tests in accordance with GB 772-1987, and the results are attached. Figure 1-4 And as shown in Table 1.

[0096] Table 1 Insulator Performance Tests

[0097]

[0098]

[0099] From Table 1 and Appendix Figure 1-4 The data shows that the present invention provides an insulator and its low-temperature sintering process, which consists of a ceramic core and a self-cleaning outer layer. The aluminum hydroxide in the self-cleaning layer is modified, and the hydrophobicity, hardness, dielectric constant, equilibrium tensile strength and elongation at break of the self-cleaning outer layer are greatly improved. Furthermore, the present invention achieves a strong bond between the self-cleaning outer layer and the ceramic core by low-temperature sintering, making it less susceptible to aging and detachment due to external environmental influences. It has strong self-cleaning ability, good insulation effect, low manufacturing cost and long service life.

[0100] The above embodiments are a limited number of preferred implementations of the present invention, and their descriptions are relatively specific and detailed, but they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention.

Claims

1. An insulator, characterized in that, It consists of a ceramic core and a self-cleaning outer layer, wherein the self-cleaning outer layer is made of the following basic raw materials in parts by weight: 100 parts of high-temperature vulcanized silicone rubber 30-60 parts aluminum hydroxide 20-40 parts zinc oxide 10-20 parts of polylactic acid-glycolic acid copolymer 5-10 parts of lanthanum oxide Vinyl bis-stearamide 4-8 parts; The polylactic acid-glycolic acid copolymer is composed of 50-75% lactic acid and 25-50% glycolic acid; The high-temperature vulcanized silicone rubber is methylphenyl vinyl silicone rubber, with a phenyl content of 15-25 mol% and a vinyl content of 0.16%-0.23%. The low-temperature sintering process of the above insulators: (1) Preparation of modified aluminum hydroxide: Polylactic acid-hydroxyacetic acid copolymer and tetrachloromethane are mixed evenly to obtain a mixture. Aluminum hydroxide powder is added and ultrasonically vibrated for 5-10 min to obtain a suspension. Emulsifier is added, the mixture is stirred and filtered to obtain a filter residue. The filter residue is washed with anhydrous ethanol 3-5 times and dried in an oven at 60-80℃ to constant weight to obtain modified aluminum hydroxide. (2) Preparation of self-cleaning coating: Modified aluminum hydroxide, zinc oxide, lanthanum oxide and high-temperature vulcanized silicone rubber are mixed and ball-milled for 10-30 min to obtain mixed powder; vinyl bis-stearamide and deionized water are mixed at a mass ratio of 1:10-40, ultrasonically dispersed and stirred to obtain dispersion; the mixed powder and dispersion are mixed, high-speed sheared and ultrasonically treated to obtain self-cleaning coating; (3) Low-temperature sintering: The ceramic core is cleaned to obtain clean ceramic. A self-cleaning coating is applied to the surface of the clean ceramic to form a self-cleaning film. The ceramic is calcined at 220-260℃ for 4-8 hours and then cooled to obtain the insulator. The thickness of the self-cleaning membrane layer is 0.5-2 mm; The mass ratio of the polylactic acid-glycolic acid copolymer to tetrachloromethane is 1:2-10; The emulsifier is polyoxypropylene ether; The mass ratio of the polyoxypropylene ether to the suspension is 1:5-10; The ceramic core is a zirconia ceramic core.

Citation Information

Patent Citations

  • Superhydrophobic coating, anti-pollution-flashover superhydrophobic insulator and preparation technique thereof

    CN105820644A

  • Preparation method of self-cleaning ceramic

    CN108947584A

  • Preparation method of antifouling disc-shaped suspension type porcelain insulator

    CN113061373A